An Exploration Into Self-Harm In Light of Heideggerian and Kierkegaardian Concepts of Repetition (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
An exploration into self-harm utilising clinical experiences. Exploring how the interpretation of this behaviour has developed over time and how dependant it is upon the culture and society it is expressed in. Discussing how Heideggerian and Kierkegaardian concepts of repetition could enhance our understanding of self-harm.
Keywords: Self-harm; existential; Heidegger; Kierkegaardian; repetition; psychotherapy